Correlations for performance traits of growing boars - Conley, P.B. III; Orwig, T.W.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Performance records of 275 boars, beginning at 65 and ending at 250 lbs., were analyzed to determine correlations of performance traits. Fastest growing boars were more efficient (r=-.49). In addition, faster gaining boars also tended to have more backfat (r=.20). Backfat thickness and feed efficiency were not related (r=.0l). Average daily gain from 65 to 220 lbs. was highly correlated with average daily gain from 65 to 250 lbs. (r=.92), which suggests that boars need not be tested to heavier weights. The feed/gain ratios during both test periods likewise were highly correlated (r=.82).
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Performance traits; Boars